Adaptation strategies of farmers to increase capacity in the midst of climate change. Issue 1 (1st December 2022) - Busthanul, N; Demmalino, E B; Syafiuddin, M; Zhafran, L M; Rahmawati, Nabilah; Heliawaty,
Abstract: The objectives of this study are examining the factors that influence cocoa producers' adaptive capacity in the face of climate change in the Bantaeng district. This is a qualitative-descriptive data analysis research project. This is an analytical method for processing research findings in order to get a conclusion. Qualitative analysis is used to describe and describe cocoa farming, in addition to analyzing the adaption strategy of cocoa farmers in the research area. The findings revealed that compared to Tompobulu District, where farmers do not pay care to their cocoa trees, cocoa farmers in Gantarangkeke District pay more attention to their plants by always doing sanitation such as pruning, smoking, and other activities.